Людський розвиток в Україні : пріоритети розвитку сільських поселень у контексті децентралізації управління - Лібанова, Елла Марленівна; Макарова, Олена Володимирівна; Заяць, Тетяна Анатоліївна; Головко, Лілія Василівна; Дяконенко, Оксана Іванівна; Жаховська, Валентина Леонідівна; Пєтухова, Ольга Михайлівна; Нечитайло, Тетяна Юріївна; Краєвська, Галина Олександрівна; Танцюра, Вадим Леонідович; Терон, Ірина Василівна (My University, 2020)
Розкрито методологічні та методичні засади дослідження процесів розвитку поселень в умовах адміністративно-територіальної реформи з обґрунтуванням концептуальних засад їх пріоритизації. Розглянуто взаємозв’язок інтересів і механізм взаємодії основних суб’єктів сільського розвитку задля досягнення цілей партнерства. Обґрунтовано соціально-економічні передумови, необхідні для збалансованого розвитку сільських поселень в Україні в умовах нестабільності, запропоновано пріоритети їх розвитку на найближчу перспективу. Здійснено прогнозні оцінки щодо перспектив розвитку сільських поселень різної людності в Україні залежно від темпів адміністративно-територіальних змін у країні. Methodological and methodical bases of research of processes of development of settlements in the conditions of administrative-territorial reform with substantiation of conceptual bases of their prioritization are opened. The interrelation of interests and the mechanism of interaction of the main subjects of rural development for achievement of the purposes of partnership are considered. The socio-economic preconditions necessary for the balanced development of rural settlements in Ukraine in the conditions of instability are substantiated, the priorities of their development for the near future are offered. Predictive assessments of the prospects for the development of rural settlements of different populations in Ukraine depending on the pace of administrative and territorial changes in the country.
Keywords: розвиток; сільські поселення; партнерство; адміністративно-територіальна реформа; прогноз; development; rural settlements; partnership; administrative-territorial reform; prediction; кафедра маркетингу